Research progress on the treatment of knee osteoarthritis combined with osteoporosis by single-herb Chinese medicine and compound - Zhou, Guanghui; Zhang, Xianquan; Gu, Zhuoxu; Zhao, Jinlong; Luo, Minghui; Liu, Jun (Frontiers in Medicine, 2023)
Knee osteoarthritis (KOA) is a degenerative disease with synovial inflammation, articular surface cartilage degeneration, meniscus degeneration, ligament and muscle changes, subchondral bone changes, and osteophyte formation around the joint as the main pathological changes. Osteoporosis (OP) is a disease characterized by low bone mass and deterioration of the microstructure of bone tissue. KOA and OP are both geriatric diseases, and the incidence of KOA combined with OP is high, but there is a lack of specific drugs, and the major treatments are limited to drug therapy. Most traditional Chinese medicine (TCM) treatments use plant-based natural products, and they help patients obtain good clinical benefits and at the same time provide researchers with ideas to study the mechanism of disease occurrence and the relationship between the two diseases. This article summarizes the research progress of TCM monomers and TCM compounds that are frequently used to treat KOA combined with OP to provide ideas for future clinical treatments and related basic research.